2017
DOI: 10.1007/s10508-017-0982-9
|View full text |Cite
|
Sign up to set email alerts
|

Appearance Dissatisfaction, Body Appreciation, and Sexual Health in Women Across Adulthood

Abstract: Risk and protective factors are equally important to the promotion of sexual health. Yet, in body image and sexuality research, most of the focus has been placed on the deleterious effects of appearance dissatisfaction and body mass index (BMI) at the expense of more adaptive dimensions. Furthermore, although age can affect appearance and sexual function, little is known regarding the experience of older women. Therefore, this study was aimed at comparing how positive body image (operationalized as body apprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 73 publications
2
12
0
1
Order By: Relevance
“…Our findings indicate that appearance satisfaction seems to be a unique source of variation in sexual satisfaction in late adulthood, as has previously been documented in young adulthood (Kvalem et al, 2019; Woertman and van den Brink 2012). Although the particular body image measure used in this study has not previously been used in older age groups, our findings among Scandinavian women resemble the findings by Robbins and Reissing (2018), where body appreciation was associated with sexual satisfaction in women across all age groups (age 18-88), controlling for BMI. That appearance dissatisfaction also predicted sexual satisfaction in men is not in accordance with two previous studies including older men, where no association between body image and sexual satisfaction was found controlling for relevant factors (Penhollow et al 2009; Shkolnik and Iecovich 2013).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our findings indicate that appearance satisfaction seems to be a unique source of variation in sexual satisfaction in late adulthood, as has previously been documented in young adulthood (Kvalem et al, 2019; Woertman and van den Brink 2012). Although the particular body image measure used in this study has not previously been used in older age groups, our findings among Scandinavian women resemble the findings by Robbins and Reissing (2018), where body appreciation was associated with sexual satisfaction in women across all age groups (age 18-88), controlling for BMI. That appearance dissatisfaction also predicted sexual satisfaction in men is not in accordance with two previous studies including older men, where no association between body image and sexual satisfaction was found controlling for relevant factors (Penhollow et al 2009; Shkolnik and Iecovich 2013).…”
Section: Discussionsupporting
confidence: 71%
“…No correlation was found between body and sexual satisfaction among women, and the significant association observed among men became nonsignificant when controlling for other factors, such as frequency of orgasms, sexual self-confidence, and relationship satisfaction. Finally, Robbins and Reissing (2018) examined 215 women aged 18-88, all in a steady relationship. Women in older adulthood who experience low body appreciation reported lower levels of sexual satisfaction than women with average body appreciation, while high body appreciation was not related to sexual satisfaction.…”
Section: Body Image and Sexual Satisfactionmentioning
confidence: 99%
“…These results are in line with previous research that showed how gay men are exposed to body weight dissatisfaction, regardless of age. The results also demonstrate that BIW have to be considered as a vulnerable group; this group has been understudied [24,25,79,80]. The mediation analyses demonstrated how important the comparison of physical appearance is.…”
Section: Discussionmentioning
confidence: 76%
“…Body appreciation is also a unique predictor of better sexual functioning, including greater condom use selfefficacy, sexual assertiveness, and entitlement to pleasure (Grower & Ward, 2018), as well as more arousal, more frequent orgasm, and greater overall sexual satisfaction (Satinsky, Reece, Dennis, Sanders, & Bardzell, 2012). These associations cannot be explained by, and even supersede, associations between these positive outcomes and other, related predictors, such as body-mass index (Robbins & Reissing, 2018), age, or partner status (Satinsky et al, 2012).…”
Section: Body Appreciationmentioning
confidence: 99%